Profession, code, and ethics - Davis, Michael (Ashgate studies in applied ethics, 2002)
"This book offers a systematic analysis of professions, emphasizing not special knowledge but special obligations. Presenting a theory of professions which explains the moral authority of professional codes, this book presents an invaluable combination of systematic theory with detailed consideration of specific questions of professional ethics. Three 'professions' are chosen for comparison - lawyering, engineering and policing. Both lawyering and engineering are examined as professions in being. Davis explores what police have to do to turn their honest occupation into a profession like law or engineering, arguing that what the police lack is not education (as sociologists would propose) but a set of standards beyond that which law, market, and morality demand, to which they are willing to commit themselves."--BOOK JACKET.